Correlation analysis of the crude oil, gold and steel prices for the purpose of agricultural development - Jeremić Dejan; Stanojević Slobodan; Mihajlović Milan; Ivanova Biljana; Kostić Radan; Marjanović Nataša (Ekonomika Poljoprivrede (1979), 2022)
This paper investigates the relationship between oil, gold and steel prices observed over a period of ten years with the aim of presenting their situation and trends using statistical methods and time series over a longer period of time and their impact on agricultural development. The high share of agriculture in the basic macroeconomic aggregates of the Republic of Serbia conditions that agriculture has a significant role in the foreign trade of the Republic of Serbia, especially in exports. The negative trend of rising fuel prices per farmer reduces the average fuel consumption per hectare. Also, the growth of the price of steel is conditioned by the growth of the prices of agricultural machinery.